(untitled) (Islamic Sciences Journal, 2023)
The manuscripts did not receive noticeable attention among researchers and scholars, there for, they have been abandoned. If the curtain had been revealed about them, we would have been astonished by their precious treasures and precious sciences. Praise be to Allah - (A letter on urgent women’s expense, by Muhammad bin Mustafa Musleh Al-Din Al-Qujuwi, famous for Sheikh Zada, who died in the year 951 AH), has been completed and what distinguishes this letter: Sheikh Zadeh wrote it in the recognized academic way: a presentation of the issue, then a statement of the sayings of scholars.